Optimizing organizational performance: the vital role of workplace stress management among public servants / Yuslinda Mat Yassin - Mat Yassin, Yuslinda; Mohd Azlan, Nurul Atiqah; Abdul Rahman, Muhammad Fadhli; Mahpuz, Melina; Shahrin, Nur Aini Natasya (Faculty of Communication and Media Studies (FCMS), 2024)
Despite growing recognition of the detrimental effects of workplace stress on employee well-being and organisational outcomes, there remains a gap in understanding the specific strategies and interventions required for effective stress management among employees to enhance organisational performance. This study analyzes the vital role of workplace stress management practices and organizational performance in the public sector. It identifies key factors influencing the government’s employee stress levels and their subsequent impact on organisational outcomes in Pejabat Setiausaha Kerajaan Negeri Selangor (SUK). The study's theoretical model is based on the Transactional Model (Cognitive Appraisal) by Lazarus & Folkman (1984). To address the research questions, three objectives were formulated: first, to assess employees' comprehension of the importance of workplace stress management in organisational performance; second, to pinpoint the factors contributing to workplace stress experienced by employees; and third, to explore the influence of employees' stress management on organisational performance. Selfadministered questionnaires were distributed to employees, and 128 staff members participated in the study. Descriptive statistical approaches were used to analyse the data.